The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1146/annurev.ms.25.080195.001205
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Grain Boundaries in the High-Tc Superconductors

Abstract: KEY WORDS:weak links, bicrystals, EELS, YBa2CU307_,S, grain boundary structure A BSTRACT Grain-boundary weak links limit the critical current density of poly crystalline high-Tc superconductors. Themes that have evolved from research on these grain boundaries include (a) an apparent general and dramatic distinction between the behavior of low-angle and high-angle grain boundaries, (b) electrical heterogeneity along as well as among boundaries, (c) indications that the macroscopic current path may or may not cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
66
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 46 publications
2
66
0
Order By: Relevance
“…[10][11][12][13] Samples of HTS's are often granular in composition, consisting of superconducting grains coupled to one another by grain-boundary junctions. 14 This granularity leads to nonlinear effects such as harmonic generation ͑HG͒ and twofrequency intermodulation ͑IM͒, and also to a dependence of the surface impedance on the amplitude of the ac field. 15,16 These nonlinearities can cause various problems in device applications.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Samples of HTS's are often granular in composition, consisting of superconducting grains coupled to one another by grain-boundary junctions. 14 This granularity leads to nonlinear effects such as harmonic generation ͑HG͒ and twofrequency intermodulation ͑IM͒, and also to a dependence of the surface impedance on the amplitude of the ac field. 15,16 These nonlinearities can cause various problems in device applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, since YBa 2 Cu 3 O x can only be slightly overdoped from the optimal composition of xϭ6.94 up to xϭ7, their GBs are generally thought to be hole deficient. 10,11 Recently, Schmehl et al 12 have made Cadoped YBa 2 Cu 3 O x bicrystals where greater overdoping is possible, 13 finding that the GB resistance could be strongly decreased and J b ͑0 T, 4.2 K͒ of some 24°͓001͔ tilt GBs increased by as much as eight times. More recent work with YBa 2 Cu 3 O x /Y 0.7 Ca 0.3 Ba 2 Cu 3 O x multilayers showed that J b ͑0 T, 77 K͒ could be raised by up to 3.5 times.…”
mentioning
confidence: 99%
“…1,4,6,7 Since this range covers a PGBD separation of 4.5-0.6 nm, a more explicit test of the above models is highly desirable. 8 This issue has regained importance because of renewed activity on making conductors with a strong biaxial texture from YBa 2 Cu 3 O 7Ϫx ͑YBCO͒, using an ion beam assisted deposition process. [9][10][11] Since such conductors would be useful for the production of strong fields, provided that the spread in the a/b grain axis misalignment is controlled, knowledge of the extended high field voltage current (V -I) characteristics of YBCO bicrystals of varying misorientations is of both fundamental and applied interest.…”
mentioning
confidence: 99%